Control Strategy of Islanded AC/DC Hybrid Microgrid Power System Based on Adaptive Segmented Double-Droop - MI Yang, GU Fuyike, LI Chunxu, BAO Wei, YAN Yuehao, LIU Xiaohui, YANG Yanan (Dianli jianshe)
An adaptive segmented double-droop control strategy is proposed to improve the power-allocation accuracy of bidirectional AC/DC converters in islanded AC/DC hybrid microgrids. First，a normalization method is used to convert the AC frequency and DC voltage into the same interval to determine the transmission power of the converter. Second，to plan the operating mode of the bidirectional AC/DC converter reasonably，the load states of the AC and DC subnets are divided. By setting the action threshold to avoid frequent starts and stops，an adaptive function is selected to add the stage II droop expression when the power difference exceeds the starting threshold by maintaining the conventional double-droop control in segment I. Thus，the bidirectional AC/DC converter can attain power balance faster when the active power difference of the subnetwork is large，which improves the coordinated control ability and service life of the bidirectional AC/DC converter. The system is decoupled to verify the stability of the proposed control strategy. Finally，an islanded AC/DC hybrid microgrid is constructed in MATLAB/Simulink and RTLAB to analyze and verify the adaptive segmented double-droop control strategy proposed herein.